Synergistically enhanced interface stability by graphene assisted copper surface reconstruction. (March 2022) - Yang, K.M.; Li, Q.; Zhang, Q.; Liu, G.S.; Wang, J.J.; Yang, Y.F.; Guo, C.X.; Ni, J.M.; Song, J.; Zhang, J.; Liu, Y.; Fan, T.X.
Abstract: Graphene (Gr)/Copper (Cu) composites have shown great potential in thermal-management and information-transport applications. The influences of interface related characteristics, such as orientation, adhesion energy and localized strain are of great importance, however, rarely reported. In this work, by conducting heavy ions irradiation and thermal boundary conductance characterization (by time-domain thermoreflectance technique), we examined the intrinsic relationship between microstructural characteristics and interface stability of various Gr/Cu interfaces, such as Gr/100 Cu, Gr/111 Cu, and Gr/111/100 Cu. Here we report: (1) compared to Gr/111 Cu interfaces, Gr/100 Cu interfaces exhibit higher defect sink capability, and (2) Gr/111/100 Cu interfaces possess both high defect sink capability and good interface stability. Our atomistic simulations suggest higher interface volumetric stress of Gr/100 Cu interface. The synergistic enhancement of Gr/111 Cu and 111/100 Cu interfaces is attributed to coherent interface generated by Gr assisted Cu surface reconstruction. The present findings may provide more insight to understand the interface characteristics-stability relation of carbon/metal composites. Graphical abstract: Image, graphical abstract